Peran Bimbingan Konseling dan Program Menabung dalam Meningkatkan Literasi Keuangan Siswa MTS Ummul Quraa Kecamatan Percut Sei Tuan - Dinda Syahrani (Lembaga Pengembangan Kinerja Dosen, 2025)
Early financial management is an important skill for adolescents to form healthy financial behavior. However, observations at MTS Ummul Qura show that most students are still low in financial literacy and are not accustomed to saving. This community service was conducted to improve students' financial literacy through a combination of counseling guidance and saving practices at school. The method used is a case study with a participatory approach, involving students, counseling teachers, homeroom teachers, and school officials. Activities included financial literacy socialization, savings practice training, and regular monitoring and mentoring. The results showed an increase in financial literacy awareness, changes in consumptive behavior to be more rational, and the formation of consistent saving habits with student participation increasing from 25% to more than 70%. The program also received active support from teachers and parents, so it has the potential to become a sustainable school culture. The findings confirm that the integration of counseling and real practice is effective in building adolescent financial literacy and supporting the national financial literacy agenda.